Pas de provenance sans contexte - Peter Mark (Afriques)
If one of the aims of art history is to understand better the original meaning of the works studied, then an historical methodology is absolutely essential to the identification and interpretation of precolonial objects. This essay focuses on 16th- and 17th-century ivory carvings identified as ‘Luso-African’. Both the geographical provenance and the ‘ethnic’ or cultural origins of the presumed artists have been mistakenly identified. Geographical terms associated with the Upper Guinea Coast in the 16th century do not correspond to the region these terms are associated with today. Likewise, the term used to identify the culture of the artists, ‘Sape’, does not correspond to any contemporary group using that designation.